Ruées vers l’or au Sahara : l’orpaillage dans le désert du Ténéré et le massif de l’Aïr (Niger) - Emmanuel Grégoire; Laurent Gagnol (EchoGéo)
In the midst of a worrisome political and economical climate, a new activity suddenly and unexpectedly emerged in Northern Niger early 2014: gold panning in the Djado valley. A few months later, operations began at a second site in Tchibarakaten. Several smaller deposits were found in the Air mountain range. Gold fever spread amongst Niger’s people and foreigners seeking fortune. The present article retraces this quest for gold by describing the main gold panning sites and their operators. Relationships between the state, the traders and gold prospectors are also reviewed. Finally, the political, religious, economical and environmental consequences of clandestine gold panning activities in the Agadez region are analysed.